2020
DOI: 10.1101/2020.12.09.20246777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autocrine and paracrine interferon signaling as ‘ring vaccination’ and ‘contact tracing’ strategies to suppress virus infection in a host

Abstract: The innate immune response, particularly the interferon response, represents a first line of defense against viral infections. The interferon molecules produced from infected cells act through autocrine and paracrine signaling to turn host cells into an antiviral state. Although the molecular mechanisms of IFN signaling have been well characterized, how the interferon response collectively contribute to the regulation of host cells to stop or suppress viral infection during early infection remain unclear. Here… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…24,40 In contrast, recent works of ours pointed out when target cells are spatially segregated, e.g., in epithelium, the combined impact of autocrine and paracrine signaling can strongly suppress viral spread during early infection before the viral peak. 68,69 These types of models may be important in understanding how early interferon-alpha response or treatment determines long-term infection outcome as suggested recently by experimental studies of SARS-CoV-2 and MERS coronavirus. 64,70,71 The quantitative impact of the interferon-alpha response on SARS-CoV-2 dynamics and which aspect of the response plays a more important role still need to be resolved.…”
Section: Innate Immune Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…24,40 In contrast, recent works of ours pointed out when target cells are spatially segregated, e.g., in epithelium, the combined impact of autocrine and paracrine signaling can strongly suppress viral spread during early infection before the viral peak. 68,69 These types of models may be important in understanding how early interferon-alpha response or treatment determines long-term infection outcome as suggested recently by experimental studies of SARS-CoV-2 and MERS coronavirus. 64,70,71 The quantitative impact of the interferon-alpha response on SARS-CoV-2 dynamics and which aspect of the response plays a more important role still need to be resolved.…”
Section: Innate Immune Modelmentioning
confidence: 99%
“…One study shows that in 10% of severe COVID-19 cases, interferon-alpha was largely absent due to the presence of autoantibodies targeting interferon-alpha, 109 whereas another study 110 showed that 3.5% of patients with life-threatening COVID-19 had inborn errors in genes associated with the interferon-alpha response. Therefore, modeling that aims to better understand the role of interferon-alpha responses 68,69 and the responses to proinflammatory cytokines will be useful for designing and understanding the impact of therapeutics to mitigate severe disease.…”
Section: The Relationship Between Sars-cov-2 Viral Load Kinetics and mentioning
confidence: 99%